Fabrication and mechanical characterization of 3D woven Cu lattice materials. (15th November 2015) - Zhang, Y.; Ha, S.; Sharp, K.; Guest, J.K.; Weihs, T.P.; Hemker, K.J.
Abstract: 3D metallic lattices designed to have two distinctly different material architectures have been woven with metallic Cu wires. A vacuum soldering technique was employed to metallurgically bond the wire nodes and form stiff 3D lattice materials. The structures and mechanical properties of the as-woven and soldered lattices were characterized by optical microscopy and micro-scale mechanical property experiments. The measured in-plane shear stiffness shows good agreement with predictions from finite element (FE) models that account for variations in the manufacturing and solder bonding. The study indicates that stiffness is influenced by the percentage of bonded nodes and the location of bonding. The 3D woven lattice materials manufactured in this study exhibited a very high percentage (80%) of bonded nodes and a unique combination of stiffness and density as compared to that typically reported for ultra lightweight lattice materials. Graphical abstract: Highlights: 3D metallic lattices with two designed architectures were woven with Cu wires. A vacuum soldering technique was employed to metallurgically bond the wire nodes. Shear stiffnesses show good agreement with predictions from finite element models. A combined axial and flexural deformation state was developed in woven lattices. 3D woven lattices offer a unique combination of stiffness and density.